Konsep dan Urgensi Pancasila Sebagai Sistem Etika - Cindy Azkhya; Zahara Lutfya; Anisa Purnama Sari; Bambang Trisno (International Forum of Researchers and Lecturers, 2024)
Pancasila, as the basis of the Indonesian state, not only acts as a constitution but also as an ethical system that underlies national and state life. In the midst of the challenges of globalization and modernization, the values ​​of Pancasila are experiencing significant tests. This article explores the concept and urgency of Pancasila as an ethical system, highlighting the reasons for the need for Pancasila as a moral guide in everyday life. Through historical, sociological and political approaches, this article analyzes the dynamics and challenges faced by Pancasila as an ethical system. A deep understanding of the essence of Pancasila as a source of values ​​and the urgency of its existence in shaping national character is the main focus of the discussion.